'The trouble with sex – it always gets in the way': An evaluation of a peer-produced teenage pregnancy video. Issue 3 (1st July 2000) - Pedrazzini, Anne; McGowan, Heather; Lucking, Linda; Johanson, Richard
Abstract : This paper describes the development and pilot evaluation of a peer-produced video, produced for use as part of North Staffordshire's Personal and Social Education school programme. A number of studies carried out in the area, including a recent audit into post-coital contraception in the under 20s, have shown that young people need to know how to access contraceptive services. Background surveys also suggest that young people need to be aware of the wider issues implicit in contraception. The impetus for the video came from the Advice Centres for the under Twenties (ACT) Working Party, who produced the video together with Staffordshire University's Media Studies Department and a local high school drama group. The video was intended for use in schools, and was designed to be complimentary to an updated and standardised teaching pack, which was already in preparation. The pilot study showed the video to be beneficial as a stand-alone intervention, principally to promote active discussion on topics that might otherwise be difficult to approach. A comparison of responses before and after the educational session demonstrated an improvement in knowledge in most areas. Further objective evaluation of the combined video and teaching pack is now necessary.